2009
DOI: 10.1007/s10637-009-9359-9
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits cell proliferation during Azoxymethane-induced experimental colon carcinogenesis via Wnt/ β-catenin pathway

Abstract: The protective role of Luteolin (LUT) against Azoxymethane (AOM)-induced mouse colon carcinogenesis has been documented earlier. The aim of this study is to investigate on the mechanism of chemopreventive action exhibited by LUT employing AOM-induced colon carcinogenesis in mice as an experimental model. LUT inhibited AOM-induced colon tumorigenesis by decreasing tumor incidence and size. LUT reduced the cell proliferation by decreasing the number of Argyrophillic nucleolar organizer region (AgNOR)/nucleus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 61 publications
(67 reference statements)
5
52
0
Order By: Relevance
“…Carbohydrates moieties of glycoproteins have also been implicated in the transport of metabolites across cell membranes and also observed a direct relationship between glycoproteins and tumorigenesis (Femia et al, 2004). Previous studies from our laboratory, showed LUT decreases the incidence of aberrant crypt foci (Ashokkumar & Sudhandiran, 2008), reduces the tumor formation and inhibits the cell proliferation via Wnt/β-catenin mediated pathway (Ashokkumar & Sudhandiran, 2011) In the present study, evaluates the modulating effect of LUT on MDF, glycoconjugates and lipid peroxidation in AOM-induced colon cancer.…”
Section: Introductionmentioning
confidence: 69%
“…Carbohydrates moieties of glycoproteins have also been implicated in the transport of metabolites across cell membranes and also observed a direct relationship between glycoproteins and tumorigenesis (Femia et al, 2004). Previous studies from our laboratory, showed LUT decreases the incidence of aberrant crypt foci (Ashokkumar & Sudhandiran, 2008), reduces the tumor formation and inhibits the cell proliferation via Wnt/β-catenin mediated pathway (Ashokkumar & Sudhandiran, 2011) In the present study, evaluates the modulating effect of LUT on MDF, glycoconjugates and lipid peroxidation in AOM-induced colon cancer.…”
Section: Introductionmentioning
confidence: 69%
“…In addition, AOM-induced CRC appears to follow the concept in which tumor initiation is followed by tumor promotion and progression in a sequential manner. Specifically, AOM induces the onset of ACF, as the precursor lesion and Mucin depleted foci (Ashokkumar and Sudhandiran, 2008;Norazalina et al, 2010;Pandurangan et al, 2012) followed by the onset of adenocarcinoma (Ashokkumar and Sudhandiran, 2011;Shafie et al, 2013) most often of the distal colon, and, finally, metastasis to mesenteric lymph nodes and liver (Reddy, 2004).…”
Section: Animal Models Of Cacmentioning
confidence: 99%
“…The expression of β-catenin was downregulated by some chemopreventive agents during chemically induced CRC and in vitro (Ashokkumar and Sudhandiran, 2011;Kaur et al, 2010;Shafie et al, 2013). Aberrant activation of both STAT3 and Wnt/β-catenin (Figure 2) often occurs in malignancies, and the two pathways regulate each other in different cancer cell lines (Armanious et al, 2010;Kawada et al, 2006;Yan et al, 2008).…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…1, 2 Dimethyl hydrazine and azoxymethane (AOM) are frequently used to induce colon cancer in rodents (Prabhu et al, 2009;Norazalina et al, 2010;Nurul-Husna et al, 2010;Ashokkumar and Sudhandiran, 2011). The spectrum of AOM-induced epithelial lesions resembles those of the various types of neoplastic lesions in human CRC.…”
Section: Animal Models For Colon Cancermentioning
confidence: 99%
“…Chemopreventive agents such as Polymeric Black Tea (Patel et al, 2008) and Luteolin (Ashokkumar and Sudhandiran, 2011) both targets wnt/β-catenin pathway. Sphingadiene is a derivative of sphigolipid inhibits colon cancer by downregulating wnt/β-catenin pathway (Kumar et al, 2013).…”
Section: Wnt/β-catenin Signaling and Colon Cancermentioning
confidence: 99%